2013
DOI: 10.1111/jocn.12188
|View full text |Cite
|
Sign up to set email alerts
|

Nursing informatics competencies: assessment of undergraduate and graduate nursing students

Abstract: These results assist nurse educators in determining specific areas of informatics content that need greater focus and inclusion in the design of better nursing educational programmes. Examples of integrating competencies into existing curriculum or informatics courses are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 16 publications
0
52
1
Order By: Relevance
“…Finally, graduate students scored higher on their wireless device skills and clinical informatics attitude, 33 whereas the current study found that there were no significant differences between students and interns on these measures.…”
Section: Mean Scores and T Tests For Sanics And Patient Safetymentioning
confidence: 68%
“…Finally, graduate students scored higher on their wireless device skills and clinical informatics attitude, 33 whereas the current study found that there were no significant differences between students and interns on these measures.…”
Section: Mean Scores and T Tests For Sanics And Patient Safetymentioning
confidence: 68%
“…Entry to practice nursing informatics competencies have been developed and integrated into undergraduate nursing curriculum in Australia and Canada (Borycki & Foster, 2014). Also, more nurses are participating in graduate programs both within and outside nursing that either focus on informatics or incorporate informatics competencies into the curriculum (Choi & De Martinis, 2013;Hunter. McGonigle & Hebda, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…18 Nursing ICs, the competencies necessary for nursing informatics practice, can therefore be defined as the knowledge, skills, and attitudes to integrate nursing science, computer, and information science to Identify, collect, process, manage, communicate, and expand data, information, knowledge, and wisdom in nursing practice. 29 However, across the myriad efforts, the majority of past private and public organizations concentrated on developing and evaluating ICs for entry-level undergraduate nurses [30][31][32][33][34][35] or graduate nurses' education. 13,23,28 Public organizations including the American Nurses Association, the American Medical Informatics Association, Healthcare Information Management and Systems Society (HIMSS), the National League for Nursing, the American Association of Colleges of Nursing, and the Technology Informatics Guiding Educational Reform (TIGER) Initiative have put efforts to identify core ICs for nurses.…”
Section: Introductionmentioning
confidence: 99%